Vigan an electronic document on Vigan : the past, present and future. (Vigan Office of the Mayor, 2000)
"This CD-ROM contains Vigan's history, geography, and industry. It also includes information about Vigan's Church, foods and fiesta.
Produced during the administration of Eva Marie S. Medina, Mayor ; Liborio Arca, Vice-Mayor ; Sangguniang Bayan members ; Vigan Municipal Personnel Multi-Purpose Cooperative ; Save Vigan Ancestral Homeowner Association, Inc. and Vigan Tourism Council.
Keywords: Vigan -- History; Vigan -- Geography; Vigan -- Description and travel